2023
DOI: 10.1002/anie.202302941
|View full text |Cite
|
Sign up to set email alerts
|

meta‐Selective C−H Functionalization of Pyridines

Abstract: The pyridine moiety is an important core structure for a variety of drugs, agrochemicals, catalysts, and functional materials. Direct functionalization of C−H bonds in pyridines is a straightforward approach to access valuable substituted pyridines. Compared to the direct ortho‐ and para‐functionalization, meta‐selective pyridine C−H functionalization is far more challenging due to the inherent electronic properties of the pyridine entity. This review summarizes currently available methods for pyridine meta‐C−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…The chemo-selective and siteselective functionalization of polyheteroarene compounds is of practical value. 47 We found that the developed paraalkylation reaction exhibits excellent chemo-selectivity for more electron-rich pyridine rings in the presence of other Nheteroarenes including pyridines (26−28), pyrimidines (29), thiazoles (30), pyrazoles (31), and xanthines (32). In the first step, the more nucleophilic pyridines in these substrates underwent selective dearomative cycloaddition with DMAD and MP.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The chemo-selective and siteselective functionalization of polyheteroarene compounds is of practical value. 47 We found that the developed paraalkylation reaction exhibits excellent chemo-selectivity for more electron-rich pyridine rings in the presence of other Nheteroarenes including pyridines (26−28), pyrimidines (29), thiazoles (30), pyrazoles (31), and xanthines (32). In the first step, the more nucleophilic pyridines in these substrates underwent selective dearomative cycloaddition with DMAD and MP.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…25 Switchable functionalization of meta-and para-C−H bonds of pyridines, however, is very challenging due to their distinct reactivities. 31 Ir-catalyzed meta-and para-C−H borylation as well as Ni- catalyzed meta-and para-C−H alkenylation relied on tailormade catalysts and ligands. 9,12,32,33 A more practical example was recently disclosed by Yu, Lin, and co-workers, who reported electrochemical meta-and para-C−H carboxylation of pyridines using different types of cell setups (Scheme 1C).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A classical approach to pyridine functionalization is in situ N-activation followed by addition of a nucleophile, creating a de-aromatized electron rich intermediate such as a dihydropyridine or a Zincke imine which offer a more versatile choice of bond formation and options to subsequently re-aromatize. [6][7] The original Zincke pyridinium reaction is illustrated in Scheme 1B, whereby aryl pyridinium 3 reacts with secondary amines to give the ring-opened azahexatriene 4. [8] Exchange with an alkylamine and ring closure gives the alkylpyridinium product 5.…”
mentioning
confidence: 99%
“…A classical approach to pyridine functionalization is in situ N-activation followed by addition of a nucleophile, creating a de-aromatized electron rich intermediate such as a dihydropyridine or a Zincke imine which offer a more versatile choice of bond formation and options to subsequently re-aromatize. [6][7] The original Zincke pyridinium reaction is illustrated in Scheme 1B, whereby aryl pyridinium 3 reacts with secondary amines to give the ring-opened azahexatriene 4. [8] Exchange with an alkylamine and ring closure gives the alkylpyridinium product 5.…”
mentioning
confidence: 99%